Educating Banten's culinary MSMEs on the value of nutritional information and halal labeling - Nita Rusdiana; Fitria Budi Utami; Niluh Sekar Negari; Nirmala Sulthon S. Putri; Novia Ramadhinta; Nudrika Arwani Pasaribu (Universitas Muhammadiyah Magelang, 2024)
Many consumers seek nutritional information and halal certification on food packaging to make informed choices and build trust. However, culinary MSMEs in Banten often lack the knowledge on proper labeling procedures. To address this gap, a community service program was initiated to educate Banten's culinary MSMEs on the significance of including nutritional value and halal labels on their products. The program utilized online counseling sessions (Zoom Meetings) with discussions, Q&A sessions, and e-questionnaires. Evaluation results highlighted a high level of understanding among participants, with an average score of 91.22% for knowledge (cognitive aspect), 92.36% for attitude (affective aspect), and 90.97% for willingness to act (behavioral aspect).